The development of systolic heart failure in case of pressure overload-induced left ventricular myocardial hypertrophy is associated with a unique microRNA expression profile in a rat model. (10th June 2022) - Ruppert, M; Korkmaz-Icoz, S; Agg, B; Sayour, AA; Olah, A; Nagy, D; Benke, K; Ferdinandy, P; Merkely, B; Szabo, G; Radovits, T
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): New National Excellence Program of the Ministry of Human Capacities Introduction: Growing body of evidence suggests that distinct alterations in myocardial microRNA (miRNA) expression contribute to pressure overload (PO)-induced pathological cardiac remodeling. Nevertheless, it is still under intense investigation whether the changes in miRNA expression patterns are also associated with the decompensation of LV systolic function in case of PO-evoked LV hypertrophy (LVH). Hence, we aimed to characterize miRNA expression in PO-induced LVH with and without systolic heart failure (HF). Methods: PO was evoked by abdominal aortic banding (AB) in male Sprague-Dawley rats. Age-matched, sham-operated animals served as controls. Functional and morphological alterations were assessed by echocardiography and histology. At the end of the experimental period, rats in the AB group were subcategorized based on ejection fraction [EF] into ABLVH (EF>40%) and ABHF groups (EF<40%). Global miRNA expression profiling was performed using next generation sequencing. Bioinformatics analysis was carried out to predict miRNA-target interactions. Expression of selected target genes was measured by qRT-PCR. Results: Increased heart weight-to-tibial length, LV mass and fibrosis confirmed the development of pathological LVH in both the ABLVH and ABHF groups. Nevertheless, increased lung weight-to-tibial length, chamber dilatation and severely reduced EF was noted only in the ABHF and not in the ABLVH, when compared to the sham group. 50 miRNA showed different expression in the ABHF compared to the ABLVH group. Based on the altered gene expression profile, in silico bioinformatics analysis predicted several target genes. Among them, reduced mRNA expression level of Fmr1 (FMRP translational regulator 1), Zfpm2 (zinc finger protein, multitype 2), Wasl (WASP like actin nucleation promoting factor), Ets1 (ETS proto-oncogene 1) and Atg16l1 (Autophagy Related 16 Like 1) was confirmed in ABHF compared to ABLVH. Conclusions: Decompensation of systolic function in PO-induced LVH is associated with unique miRNA profile leading to specific regulation of gene expression.